Pernikahan Beda Agama Sebagai Fakta Sosial Dalam Perspektif Hukum Islam - Nurhayati, Dinda Siti; Siregar, Rini Wahyuni; Arif, Muhammad; Husnayani, Rahima (STAI Tebing Tinggi Deli, 2023)
This research aims to examine islamic law's perspective on interfaith marriage as social fact. The method used is qualitative, with a descriptive approach. As a social fact, some people legalize interfaith marriages in various ways: marry abroad, marriage registration is carried out at one of the KUA or KCS with one partner